The effects of computer games on the academic performance of CSC134 students in UiTM Terengganu Dungun Campus / Nor Azila Awang Abu Bakar, Nazatul Azleen Zainal Abidin and Norlina Mohd Sabri - Abu Bakar, Nor Azila Awang; Zainal Abidin, Nazatul Azleen; Mohd Sabri, Norlina (Institute of Research, Development and Commercialization, 2008)
Computer games have reached the lives of millions of people worldwide. Today, these games have become a popular source of entertainment especially to students. Therefore, this research is intended to study the effects of playing computer games on noncomputer science students' performance particularly in a computer-related subject at UiTM Terengganu. This research goes through five activities: (1) Review previous research to determine significance of the next research, (2) Preliminary study on category of computer games, (3) Develop and disseminate research instruments, (4) Analyze collected data using statistical methods, and (5) Conclusion and documentation. Questionnaires were distributed to CSC134 students where their background and experience were evaluated in order to seek information on their habitual patterns of playing computer games and understand how computer games might affect them in their studies. The result shows that more than half of the students like to play computer games. A majority of these students prefer playing Card and Arcade type of games and spent time playing at least twice a week for the duration of more than three hours each time. One of the important findings is that early exposure to computer games does not have any profound effect on overall students' achievement in CSC134. However due to the familiarization of using computers, the students performed better in their laboratory assessments. Even though playing games does not assure good results in CSC134 course, nearly 88% of them passed the course.